2020
DOI: 10.3390/nu13010076
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Food Craving, Appetite-Related Hormones and Clinical Parameters in Bipolar Disorder

Abstract: Obesity and weight gain in bipolar disorder (BD) have multifactorial underlying causes such as medication side effects, atypical depressive symptomatology, genetic variants, and disturbances in the neuro-endocrinal system. Therefore, we aim to explore the associations between food craving (FC), clinical parameters, psychotropic medication, and appetite-related hormones. In this cross-sectional investigation, 139 individuals with BD and 93 healthy controls (HC) completed the food craving inventory (FCI). In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…However, previous research has shown contradictory results regarding ghrelin levels of patients with BD. Rosso et al 25 observed that ghrelin levels were lower in patients with BD than in healthy controls, whereas Platzer et al 26 and Tunçel et al 27 reported no difference in ghrelin levels between patients with BD and healthy controls. However, Tunçel et al 27 observed that patients with BD had significantly higher ghrelin levels during euthymic episodes than during manic episodes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown contradictory results regarding ghrelin levels of patients with BD. Rosso et al 25 observed that ghrelin levels were lower in patients with BD than in healthy controls, whereas Platzer et al 26 and Tunçel et al 27 reported no difference in ghrelin levels between patients with BD and healthy controls. However, Tunçel et al 27 observed that patients with BD had significantly higher ghrelin levels during euthymic episodes than during manic episodes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of central circuits in the expression of LepRls sheds light on the integration of metabolism as a contributing factor for feeding and stress-related neuropsychiatric disorders [ 95 , 96 , 97 , 98 ]. The function of leptin in the CNS requires fine-tuning of LepRls signaling throughout the neuroendocrine axes, which is a coadjutant in the physiopathology of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Presence of food cravings: Individuals with BD report more frequent food cravings, mostly for foods high in fat, sodium and refined carbohydrates. In addition, the presence of more frequent food cravings in BD is associated with increased depressive symptoms and negatively correlates with ghrelin levels (Platzer et al, 2020).…”
Section: The Emotional Eating Ebpmentioning
confidence: 99%
“… Presence of food cravings: Individuals with BD report more frequent food cravings, mostly for foods high in fat, sodium and refined carbohydrates. In addition, the presence of more frequent food cravings in BD is associated with increased depressive symptoms and negatively correlates with ghrelin levels (Platzer et al, 2020 ). Excessive consumption of highly palatable foods: Palatable foods are known to activate the brain's reward circuitry similarly to drugs of abuse and dopamine signaling impacts both food intake and mood (Singh, 2014 ).…”
Section: Eating Behavioral Phenotypes In Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation